The voice of French existential on constructions - Marc Authier; Lisa A Reed (Isogloss)
The external arguments of short passives and French existential on constructions share strikingly similar properties: both display discourse and scopal inertness, both fail to provide an antecedent for a PRO subject of a passive infinitival, and neither is compatible with an unaccusative verb. Such similarities have yet to be fully explained. Using Merchant’s (2013) observation that ellipsis is subject to identity between phrase markers, we argue that existential on sentences contain a non-active Voice head that existentially binds an external argument that remains syntactically unprojected, just as Bruening (2013) argues is the case for short passives. We further argue that on is the default agreement spellout that obtains when tensed T fails to find a goal bearing the appropriate valued j-features, assuming with Preminger (2009, 2014) that when Agree fails, the unvalued features on the probe retain their preexisting or default values. Finally, we argue that EPP in existential on constructions is satisfied on the assumption that it reduces to An’s (2007) Intonational Phrase Edge Generalization (IPEG) and we show that IPEG, combined with our theory of existential on, correctly predicts the existence of a silent counterpart to existential on in ECM contexts.